Market participation of smallholder sunflower farmers in Sekhukhune District of Limpopo Province, South Africa - Mathagu, Hangwelani Tshilidzi (My University, 2016)
The study focused on the market participation of the smallholder sunflower farmers of Sekhukhune District in Limpopo Province of South Africa. A total of 100 smallholder sunflower farmers of Sekhukhune were randomly selected for the study. Data was gathered through the use of structured questionnaires with open-ended questions. The data was analysed using the Logistic Regression model on SPSS 26.0 (statistical package for social sciences). The probability of the smallholder sunflower farmers participating in markets was determined significantly by gender of household head, farm size, level of education, marketing experience, distance to the market, ownership of vehicle and stakeholder availability. Recommendations were made with regard to that of training, monitoring, funding, Government support, access to production land and the involvement of organizations with the smallholder sunflower farmers. Training should be provided for the smallholder sunflower farmers because farmers are always faced with new technology and market changes, there should be a budget that is put aside for the funding of the smallholder farmers, monitoring programs should be implemented in order to monitor the progress of the smallholder farmers, increased access to production land for farming, government support through financial and input support, smallholder farmers should get involved with organizations that can help them with training and funding, and the government should implement policies that are commodity based. Key words: smallholder farmers, market participation, Logistic Regression Model, sunflower, Limpopo province
Thesis (MSc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2016
Keywords: Small holder farmers; Markets; Sunflower; Agriculture -- South Africa -- Limpopo; Markets; Agriculture -- Economic aspects -- South Africa -- Limpopo.; Agricultural development projects